Priredbe in skrajšave literarnih besedil, primerne za otroke z okvaro sluha ter otroke z govorno-jezikovnimi motnjami - Vizjak Puškar, Nika (Jezik in slovstvo, 2017)
The article deals with the problem of adapting texts for children with special needs, focusing mainly on children with speech and language disorders. The first part presents the theoretical aspects of literary adaptations and specifications for the adaptations of texts for people with special needs in the field of language. We then present the existing literary adaptations for this population published in the Slovenian language. The second part of the discussion presents part of a case study that was carried out directly during the teaching of Slovenian at the Maribor Centre for Hearing and Speech, during which 8th grade students with speech and language disorders read Tavčar's Visoška kronika.
Keywords: Tavčar, Ivan, 1851-1923; "Visoška kronika"; children's literature; otroška književnost; literarne priredbe; posebne potrebe; govorno-jezikovne motnje; Slovene literature; slovenska književnost